The role of internal audit in the functioning of an effective system of internal control of enterprises - I. I. Chebyshev (Publishing House of the State University of Management, 2021)
The author carried out research of the list of issues related to the field of internal audit, namely its role in achieving the effectiveness of the internal control system. The article logically emphasizes the significance of the research area, discloses the objectives and procedure for conducting internal audit. The paper reveals the issues of the organization and functioning of internal audit as a tool for solving the problems of the company in order to increase the efficiency of its activities and investment attractiveness. From a scientific point of view, the study becomes relevant due to the problems presented and the proposed solutions. Among the identified problems there are such as inefficiency of internal audit, errors of subordination, etc.